2017
DOI: 10.1063/1.4999800
|View full text |Cite
|
Sign up to set email alerts
|

Two-component additive manufacturing of nanothermite structures via reactive inkjet printing

Abstract: With an eye towards improving the safety of the deposition of energetic materials while broadening the scope of materials compatible with inkjet printing, this work demonstrates the use of combinatorial inkjet printing for the deposition of energetic materials. Two largely inert colloidal suspensions of nanoaluminum and nanocopper (II) oxide in dimethylformamide with polyvinylpyrrolidone were sequentially deposited on a substrate using piezoelectric inkjet printing. The materials were deposited in such a way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…To increase safety during processing, Murray et al proposed combinatorial or reactive inkjet printing [77], where two components of the reactive mixture are suspended in different inks and jetted sequentially. The authors demonstrated the value of this approach by depositing nano-Al (3.5 vol.…”
Section: Inkjet Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase safety during processing, Murray et al proposed combinatorial or reactive inkjet printing [77], where two components of the reactive mixture are suspended in different inks and jetted sequentially. The authors demonstrated the value of this approach by depositing nano-Al (3.5 vol.…”
Section: Inkjet Printingmentioning
confidence: 99%
“…Another feature of additive manufacturing is the expanded capability of mixing the components. As discussed in the review, mixing can be performed during deposition by using several nozzles with their own inks, such as reactive inkjet printing [77] or sputtering in an alternative fashion [105]. More complicated design of the composites has been achieved with manufacturing of core-shell structures.…”
Section: Progress In Additive Manufacturing Of Energetic Materialsmentioning
confidence: 99%
“…[5] This has been applied to control mechanical, [6][7][8][9][10] optical, [11][12][13] and electronic [14][15][16] properties of materials, as well as enable new functional materials. [21][22][23][24][25] RMs are a subset of energetic materials and are composites that, upon ignition, give rise to the rapid liberation of energy in the form of heat and/or pressure. [21][22][23][24][25] RMs are a subset of energetic materials and are composites that, upon ignition, give rise to the rapid liberation of energy in the form of heat and/or pressure.…”
Section: D Printed Thermitementioning
confidence: 99%
“…[17][18][19][20] While a large portion of studies focus on quasi-static applications, additive manufacturing (AM) has also shown promise as a means to tailor dynamic properties, such as the rate of chemical energy release in reactive materials (RMs). [21][22][23][24][25] RMs are a subset of energetic materials and are composites that, upon ignition, give rise to the rapid liberation of energy in the form of heat and/or pressure. Further within the subset of RMs, materials can be defined as either intermetallics (metal/metal) or thermites (metal/metal oxide).…”
Section: D Printed Thermitementioning
confidence: 99%
See 1 more Smart Citation